The business-oriented CIO : a guide to market-driven management - Tillmann, George (John Wiley & Sons, 2008)
The Business-Oriented CIO: A Guide to Market-Driven Management introduces the Market Driven Management approach, which applies and adapts some of the best for-profit business thinking for use by CIOs and IT managers. IT departments are integral parts of businesses; if the electronic components like e-commerce sites fail, the business will come to a screeching halt. Run your IT department like a business rather than a reactive entity that only functions to fix problems, and transform your image from that of service center to a true business partner.